Perspectives from American Society of Clinical Oncology: translational and clinical research highlights in breast and colorectal cancers. (October 2014) - Fontanella, Caterina; Aprile, Giuseppe; Scartozzi, Mario; Lederer, Bianca; Cascinu, Stefano; von Minckwitz, Gunter
2014 ASCO Annual Meeting, Chicago, IL, USA, 28 May–3 June 2014: Advances in translational and clinical research have improved our understanding of breast and colorectal cancers, and have enabled remarkable progress in their treatment. These advances continue to be of paramount importance for breast and colorectal cancers. This report will describe and comment on the key messages from selected abstracts presented at the 50th American Society of Medical Oncology annual meeting that will impact clinical practice in the near future.